PENGARUH BUDAYA ORGANISASI TERHADAP SEMANGAT KERJA KARIAWAN PADA PT. YUDHISTIRA PALEMBANG - Suprapto, Suprapto; Zaidun, Zaidun (Jurnal Trisna Riset, 2022)
The availability of quality human resources and a high work ethic is the main capital for an organization to be on par with other organizations. One of the key factors that influences the success of an organization is organizational culture. A strong and positive culture can create a supportive work environment, increasing employee motivation and morale. PT. Yudhistira Palembang, as a company operating in the field of book publishing and distribution, faces challenges in creating an organizational culture that supports employee morale. organizational culture has not been implemented well so that employee morale is not optimal. The problem faced is how organizational culture influences employee morale at PT. Yudhistira Palembang. The purpose of this research is to determine the influence of organizational culture on employee morale at PT. Yudhistira Palembang and is useful as reference material for further research regarding organizational culture and employee morale. The hypothesis proposed is that organizational culture has a positive effect on employee morale at PT. Yudhistira Palembang. Data collection and processing using library studies and field studies using observation, questionnaires, interviews and documentation. From the results of the discussion, a correlation was obtained between organizational culture in an effort to increase employee morale at PT. Yudhistira Palembang obtained an r number of r 0.65. After consulting with conservative standards, it is between 0.600-0.799 which is considered a strong correlation. So it can be said that there is a strong influence between organizational culture on employee morale at PT. Yudhistira Palembang.